Vibronic exciton model for low bandgap donor-acceptor polymers - Balooch Qarai, Mohammad; Chang, Xin; Spano, F C (The Journal of chemical physics, 2020)
A vibronic exciton model is introduced to describe the excited state band structure and associated absorption spectra of low bandgap donor-acceptor conjugated polymers. The Hamiltonian is represented in a diabatic basis consisting of Frenkel-like donor and acceptor fragment excitations as well as charge-transfer (CT) excitations between neighboring fragments. States are coupled to each other through electron and hole transfer as well as Coulombically, through interacting fragment transition dipole moments. Local vibronic coupling involving the prominent aromatic-quinoidal vibrational mode, which is responsible for pronounced vibronic progressions in most conjugated oligomers and polymers, is also included. The DAD repeat unit is shown to behave like a J-aggregate trimer, driven by both the sizable in-phase electron and hole transfer integrals between donor and acceptor fragments as well as negative Coulomb coupling between donor and acceptor fragment excitations. The J-aggregate behavior is enhanced in the polymer limit through inter-repeat unit coupling, with the 0-0 vibronic peak significantly enhanced in the lowest-energy near-IR band. In addition, the radiative rate is enhanced by the number of coherently connected repeat units. The near-IR band is shown to possess roughly equal admixtures of CT and Frenkel-like excitations. Applications are made to the polymer PffBT4T-2DT, with the simulated absorption spectrum quantitatively capturing the salient features of the measured spectrum.